2021
DOI: 10.1002/erv.2863
|View full text |Cite
|
Sign up to set email alerts
|

Feeling imperfect and imperfectly feeling: A network analysis on perfectionism, interoceptive sensibility, and eating symptomatology in anorexia nervosa

Abstract: Objective In recent years, the network analysis (NA) methodology has been applied to identify the central features of the psychopathology of anorexia nervosa (AN) and specific connections to previously recognized vulnerabilities. However, an NA investigating both multidimensional perfectionism and interoceptive sensibility in connection to eating symptomatology is currently missing. Method A total of 260 individuals (139 patients with AN, 121 healthy control individuals) completed the Frost Multidimensional Pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 74 publications
(128 reference statements)
3
27
1
Order By: Relevance
“…In line with the application to other mental disorders, various research goals can be identified among the existing literature about network approaches to EDs, namely: validation of the transdiagnostic model of eating disorders by comparing network characteristics across ED diagnoses (DuBois et al, 2017; Forrest et al, 2018; Goldschmidt et al, 2018; Mares et al, 2021; Monteleone, Tzischinsky, et al, 2022; Solmi et al, 2018; Solmi et al, 2019); estimation of the symptom network of EDs and identification of the core symptoms (Beauchamp et al, 2021; Forbush et al, 2016; Forrest et al, 2018; Forrest, Perkins, et al, 2019; Rodgers et al, 2018; Wang et al, 2019); identification and interaction with nonspecific ED symptoms (i.e., the external field) like general psychiatric symptoms, personality traits and other clinical variables (Monteleone, Mereu, et al, 2019; Solmi et al, 2018; Solmi et al, 2019), embodiment dimensions (Cascino et al, 2019), childhood maltreatment (Liebman et al, 2021; Monteleone, Cascino, et al, 2019; Monteleone, Tzischinsky, et al, 2022; Rodgers et al, 2019), mentalizing and empathy (Monteleone et al, 2020), vulnerability factors (Vervaet et al, 2021), suicidal thoughts and behaviors (Smith et al, 2020), perfectionism and interoceptive sensibility (Martini et al, 2021), affective and metacognitive symptoms (Aloi et al, 2021; Wong et al, 2021), interoceptive awareness (Brown et al, 2020), sleep disturbance (Ralph-Nearman et al, 2021), well-being domains (de Vos et al, 2021), inflexible and biased social interpretations, socioemotional functioning (Bronstein et al, 2022); assessment of psychiatric comorbidities such as depression and anxiety (Bronstein et al, 2022; Elliott et al, 2020; Kenny et al, 2021; Levinson et al, 2017; Sahlan, Williams, et al, 2021; Smith et al, 2019), posttraumatic stress disorder (Liebman et al, 2021; Vanzhula et al, 2019), social anxiety disorder (Levinson et al, 2018a; Sahlan, Keshishian, et al, 2021), obsessive-compulsive disorder (Giles et al, 2022; Kinkel-Ram et al, 2021; Meier et al, 2020; Vanzhula et al, 2021), trait anxiety disorder (Forrest, Sarfan, et al, 2019), autism spectrum disorder (Kerr-Gaffney et al, 2020), borderline personality disorder (De Paoli et al, 2020), and alcohol misuse (Cusack et al, 2021); comparison of estimated network structures among clinical and nonclinical (Vanzhula et al, 2019),...…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In line with the application to other mental disorders, various research goals can be identified among the existing literature about network approaches to EDs, namely: validation of the transdiagnostic model of eating disorders by comparing network characteristics across ED diagnoses (DuBois et al, 2017; Forrest et al, 2018; Goldschmidt et al, 2018; Mares et al, 2021; Monteleone, Tzischinsky, et al, 2022; Solmi et al, 2018; Solmi et al, 2019); estimation of the symptom network of EDs and identification of the core symptoms (Beauchamp et al, 2021; Forbush et al, 2016; Forrest et al, 2018; Forrest, Perkins, et al, 2019; Rodgers et al, 2018; Wang et al, 2019); identification and interaction with nonspecific ED symptoms (i.e., the external field) like general psychiatric symptoms, personality traits and other clinical variables (Monteleone, Mereu, et al, 2019; Solmi et al, 2018; Solmi et al, 2019), embodiment dimensions (Cascino et al, 2019), childhood maltreatment (Liebman et al, 2021; Monteleone, Cascino, et al, 2019; Monteleone, Tzischinsky, et al, 2022; Rodgers et al, 2019), mentalizing and empathy (Monteleone et al, 2020), vulnerability factors (Vervaet et al, 2021), suicidal thoughts and behaviors (Smith et al, 2020), perfectionism and interoceptive sensibility (Martini et al, 2021), affective and metacognitive symptoms (Aloi et al, 2021; Wong et al, 2021), interoceptive awareness (Brown et al, 2020), sleep disturbance (Ralph-Nearman et al, 2021), well-being domains (de Vos et al, 2021), inflexible and biased social interpretations, socioemotional functioning (Bronstein et al, 2022); assessment of psychiatric comorbidities such as depression and anxiety (Bronstein et al, 2022; Elliott et al, 2020; Kenny et al, 2021; Levinson et al, 2017; Sahlan, Williams, et al, 2021; Smith et al, 2019), posttraumatic stress disorder (Liebman et al, 2021; Vanzhula et al, 2019), social anxiety disorder (Levinson et al, 2018a; Sahlan, Keshishian, et al, 2021), obsessive-compulsive disorder (Giles et al, 2022; Kinkel-Ram et al, 2021; Meier et al, 2020; Vanzhula et al, 2021), trait anxiety disorder (Forrest, Sarfan, et al, 2019), autism spectrum disorder (Kerr-Gaffney et al, 2020), borderline personality disorder (De Paoli et al, 2020), and alcohol misuse (Cusack et al, 2021); comparison of estimated network structures among clinical and nonclinical (Vanzhula et al, 2019),...…”
Section: Resultsmentioning
confidence: 99%
“…identification and interaction with nonspecific ED symptoms (i.e., the external field) like general psychiatric symptoms, personality traits and other clinical variables (Monteleone, Mereu, et al, 2019; Solmi et al, 2018; Solmi et al, 2019), embodiment dimensions (Cascino et al, 2019), childhood maltreatment (Liebman et al, 2021; Monteleone, Cascino, et al, 2019; Monteleone, Tzischinsky, et al, 2022; Rodgers et al, 2019), mentalizing and empathy (Monteleone et al, 2020), vulnerability factors (Vervaet et al, 2021), suicidal thoughts and behaviors (Smith et al, 2020), perfectionism and interoceptive sensibility (Martini et al, 2021), affective and metacognitive symptoms (Aloi et al, 2021; Wong et al, 2021), interoceptive awareness (Brown et al, 2020), sleep disturbance (Ralph-Nearman et al, 2021), well-being domains (de Vos et al, 2021), inflexible and biased social interpretations, socioemotional functioning (Bronstein et al, 2022);…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations